Integrated assessment of growth performance, carcass characteristics, and economic efficiency of three broiler strains raised under humid-tropical conditions - Dennis Owusu Acheampong; Kwaku Adomako; Bismark Kyei (PLoS ONE, 2026)
This study evaluated the growth performance, carcass characteristics, economic efficiency, health status, and growth patterns of three commercial broiler strains (Hubbard, Cobb 500, and Ross 308) reared under humid tropical conditions in Ghana. A total of 300 day-old chicks were allocated to a completely randomized design with five replicate pens per strain and reared for six weeks under uniform management conditions. Performance traits, carcass and internal organ characteristics, mortality, and morbidity were assessed, and growth patterns were modeled using the Gompertz function. Although initial body weights differed among strains, no significant differences were observed in final body weight, weight gain, feed intake, feed conversion ratio, or feed cost per kg weight gain. Carcass characteristics were also comparable across strains. Cobb 500 exhibited numerically higher growth rate and asymptotic weight based on the Gompertz model, whereas Ross 308 showed slower growth but lower mortality and greater development of digestive organs, suggesting improved adaptability to tropical conditions. Overall, the findings indicate that while the three broiler strains demonstrate similar production performance under tropical conditions, differences in growth dynamics and survivability may influence strain suitability. These results highlight the importance of balancing growth efficiency with environmental adaptability when selecting broiler genotypes for humid tropical production systems.